THE WEIGHTS OF MALE CROSSBREED NURSING PIGLETS AFTER GIVEN FEED ENZYMES AND TURMERIC FLOUR - Merdana, I Made; Sudira, I Wayan; Putra, Gede Yuda Darmadi (Buletin Veteriner Udayana, 2019)
This study aims to determine the effect of the addition of feed enzymes containing xylanase, amylase and protease with turmeric flour ( Curcuma domestica ) to increase the body weight of male crossbreed nursing piglets. Using a completely randomized design, thrty-two male crossbreed piglets aged four weeks weighing 7-9 kg were divided into four groups (P0, P1, P2 and P3) with eight replications. The enzymes and turmeric flour are given through feed for five weeks. Group P0 as a control given feed without treatment. Group P1 was given enzyme dose 0.1% of feed. Group P2 was given turmeric flour dose 1% of feed. Group P3 was given a combination of enzymes and turmeric flour with a dose 0.1% and 1% of feed. Data on absolute growth of piglets was obtained from the difference in weighing the initial with the final body weight. The mean of body weight gain as follows P0 = 14.81 ± 1.11; P1 = 15.99 ± 1.79; P2 = 16.94 ± 0.84 and P3 = 17.68 ± 1.62 kg. Statistical analysis showed that the addition of enzymes and turmeric flour through feed had a significant effect on the weight of the nursing piglets. The best results on the combination treatment of feed enzymes and turmeric flour with a dose of 0.1% and 1% of feed.